A new vision of classifying Quranic collocations: a syntactic and semantic perspective - Obeidat, Adham Mousa; Ayyad, Ghada Rajeh; Tengku Sepora Tengku Mahadi (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this paper, an attempt is made to revisit the term “collocation” and its classifications in the Noble Quran. It provides a new fairly detailed analysis of the features and classifications of Quranic collocations. Many studies have discussed collocations in Arabic and Quranic collocations; yet this study constitutes a new vision of classifying collocations from semantic and syntactic perspectives. The paper finds out that Quranic collocations have distinctive semantic features that worth to be studied deeply especially when used in other types of text or genre. The found features, flexibility of constituting patterns, restrictedness in all types of texts, the possibility of figurative meaning and the multiplicity of meaning when used in other types of texts, are a part of many other linguistic or semantic features of Quranic collocations. By studying the collocations function in Quran, the study points out that collocations can be classified semantically into acts of worship collocations, divine collocations and rhetorical collocations. Each group of those collocations has its syntactic patterns that should be studied deeply. These remarked findings and recommendations may enhance the understanding of the linguistic features of Quran, enhance the quality of translation of Quran and motivate further researchers to investigate this important area in Arabic and Quran.